2016
DOI: 10.3727/096368916x691150
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Stem Cell Transplantation-Mediated Alteration of Microglial/Macrophage Phenotypes after Traumatic Brain Injury

Abstract: Neural stem cells (NSCs) promote recovery from brain trauma, but neuronal replacement is unlikely the sole underlying mechanism. We hypothesize that grafted NSCs enhance neural repair at least partially through modulating the host immune response after traumatic brain injury (TBI). C57BL/6 mice were intracerebrally injected with primed human NSCs (hNSCs) or vehicle 24 h after a severe controlled cortical impact injury. Six days after transplantation, brain tissues were collected for Western blot and immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 50 publications
(65 reference statements)
2
49
0
1
Order By: Relevance
“…13 This transplantation reduced microglial activation and diminished inflammatory mediators. 13 These results pose further interesting applications of hNSC culture for transplantation and mediation of glial responses. The role of glial progenitors and transplantation is critically important due to their proven role in rescuing myelination phenotype in mice.…”
Section: Discussionmentioning
confidence: 99%
“…13 This transplantation reduced microglial activation and diminished inflammatory mediators. 13 These results pose further interesting applications of hNSC culture for transplantation and mediation of glial responses. The role of glial progenitors and transplantation is critically important due to their proven role in rescuing myelination phenotype in mice.…”
Section: Discussionmentioning
confidence: 99%
“…30,[76][77][78] In other TBI and stroke models, cells have been delivered via intravenous (IV), intra-arterial carotid (IAC) or intraparenchymal (IP) injections. However, IV administration causes loss of the majority (~95%) of the cells during lung passage, 55,[79][80][81] whereas IAC injection carries the risk of causing embolic brain infarction and fails to deliver sufficient cells across the vascular wall barrier to the brain parenchyma, which is the major barrier for putative clinical use of this route.…”
Section: 75mentioning
confidence: 99%
“…1,[23][24][25] Several preclinical studies have evaluated the efficacy of rodent neural precursor cells in TBI rodent models. 22,[26][27][28][29][30] The culturing NSCs in vitro started as an attempt to grow multipotent embryonic cortical tissue (the word neural stem cells was not yet coined) and successfully accomplished in 1989 at the University of Miami. 31 This work evolved when Martin Raff, a Canadian born Boston neurologist decided to move to England and chose to leave the United States (US) than fight in Vietnam War and to pursue immunology.…”
Section: Step 1 Cell Therapy Candidatementioning
confidence: 99%
See 1 more Smart Citation
“…116 Gao et al reported that grafted human NSCs promoted the switch of microglia/macrophages into an anti-inflammation phenotype which may contribute to stem cell-mediated neuroprotective effects after severe TBI in mice. 117 Although there is no clinical trial concerning NSC transplantation for TBI recovery, the clinical study in traumatic cervical spinal cord injury has shown the safe outcomes. 118 Transplantation of embryonic stem cells (ESCs) in TBI has also been studied.…”
Section: Neurorestorationmentioning
confidence: 99%